Website Information System for the Civil Service Police Unit for Enforcing Regional Regulations and Gubernatorial Regulations - Pancar Rahmad Adi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The rapid development of information technology has encouraged public institutions to utilize web based systems as effective communication and publication media; however, the Civil Service Police Unit (SATPOL PP), particularly the Division of Regional and Gubernatorial Regulation Enforcement, still relied on conventional promotional tools that limited information accessibility and transparency. This study aims to design and implement a company profile website as an institutional information medium to enhance public access to organizational data and activities. The research employed observation, interviews, and literature review to collect system requirements, followed by system design and development using web technologies including PHP, MySQL, and HTML. The implemented system provides structured information regarding institutional profiles, organizational structure, duties and functions, vision and mission, news updates, and contact details, supported by an administrative interface for data management. The results demonstrate that the website functions as an effective and efficient information platform that is widely accessible via the internet, improves transparency, and optimizes information dissemination. Moreover, the system contributes to operational cost efficiency by reducing dependence on printed media such as brochures and pamphlets. In conclusion, the implementation of the company profile website supports institutional performance by delivering information in a more modern, accessible, and sustainable manner.